Pengaruh Beban Terhadap Stres yang Dialami Keluarga Dalam Merawat Pasien Gangguan Jiwa - Fajar Rinawati; Sucipto Sucipto (Akademi Keperawatan Dharma Husada Kediri, 2017)
Patients with mental disorders in community (a family) will have impact on the family, the environment, and the other, such as Puskesmas, Dinkes, and Goverment. The graetest impact is on the family, because they live together with the patient everyday. the main problem that arises in the family is the burden and stress in caring the patient. The purpose of this research is to see whether there is an influence of the burden on the stress of the family who caring the patient with mental disorder at home. The research design used is a quantitative design with cross sectional approach. The sample of this research is a family that caring the patient with mental disorder, with a sample zise of 30 respondens. The results showed that the burden significantly affects to the stress, with p-value 0.008. every family who caring the patients with mental disorder must have felt the burden, both the visible and the invisible. This burden will cause stress to the family, so need cooperation to the others, such as all family members, the environment, Puskesmas, Dinkes, and Goverment.